A Novel and Severe Clinical Picture Related to COVID-19: Multi-Inflammatory Syndrome in Children - Fatih Haşlak; Mehmet Yıldız; Sezgin Şahin; Amra Adrovic Yıldız; Kenan Barut; Özgür Kasapçopur (Trends in Pediatrics)
Preliminary data have suggested that children have milder COVID-19 disease course compared to adults. However, pediatric cases with severe clinical findings caused by Severe Acute Respiratory Syndrome Coronavirus-2 (SARS-CoV-2) are being reported since April 2020. These children have been presented with significant hyperinflammatory states resembling Kawasaki disease, toxic shock syndrome, and macrophage activation syndrome. However, they had several distinct features, as well. Therefore, this novel condition was considered a unique disease and named Multi-inflammatory syndrome in children (MIS-C). Thus, new concerns have been raised regarding the vulnerability of the children. However, it has been realized that this condition is extremely rare. Nonetheless, considering that it is a life-threatening disease and may cause devastating consequences, clinicians should be aware of MIS-C while evaluating children with persistent fever and history of COVID-19 contact or active infection.